Abrasive grain ordered arrangement honing oil stone and its manufacturing method

CN121156899BActive Publication Date: 2026-10-23ZHENGZHOU HONGTUO PRECISION TOOLS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511419559.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2026-10-23
Estimated Expiration
2045-09-30

AI Technical Summary

Technical Problem

[0004]为了改善金刚石与金属材料的界面结合性能,一些科技工作者对金刚石表面镀覆一层金属,如中国发明专利CN102229097B“一种珩磨砂条”对金刚石磨粒进行镀Ni预处理;由于镀Ni活性大,在烧结过程中,其很容易进入珩磨油石的金属基体,如与金属结合剂中的Cu、Sn等金属形成脆性金属间化合物,另外镀Ni还会引起金刚石的石墨化,从而影响珩磨油石珩磨性能

Benefits of technology

Si3N4、AlN、Al2O3高温反应生成Si4Al2O2N6相,形成晶间桥接结构,填充立方氮化硼颗粒间隙,提升致密度,抑制微裂纹扩展。Al2O3细化晶粒,提高断裂韧性,CeO2作为烧结助剂与净化剂,促进液相烧结,降低烧结温度,净化晶界,增强立方氮化硼结合相界面结合强度,制备出致密的立方氮化硼聚晶烧结体,氮化硼依然保持立方结构,具有极高的强度和良好的力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121156899B_ABST
    Figure CN121156899B_ABST
Patent Text Reader

Abstract

The application provides a honing oilstone with ordered abrasive grains and a manufacturing method thereof, and belongs to the technical field of oilstones. Alloy powder, ceramic powder, silicon-plated tungsten diamond, polycrystalline cubic boron nitride and ethanol are mixed and ball milled, uniformly ultrasonically dispersed, hot-pressed and sintered to obtain a base body, and the honing oilstone with ordered abrasive grains is prepared through pretreatment, surface activation, electrodeposition and post-treatment processes. The product is mainly used for machining of precise and complex metal workpieces with high hardness, such as automobile engine cylinder blocks, hydraulic oil cylinders and bearing rings, and is used for replacing imported precision honing oilstones in the oil pump nozzle industry, so that the domestic substitution of precision honing oilstones is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of honing stone technology, specifically to a honing stone with ordered abrasive grain arrangement and its manufacturing method. Background Technology

[0002] Honing is a fundamental process in precision machining, and its technical level directly relates to the performance limits of high-end equipment. Honing is mainly used for the finishing of the inner surface of ultra-hard workpieces such as ferrous metals, hardened steel, high-speed steel, stainless steel, nickel-chromium alloys, chromium alloys, and titanium alloys. Through rotation and reciprocating motion, a uniform cross-hatching pattern is formed, removing minute excess material from the workpiece surface to achieve a mirror-like finish. Honing is fundamental to precision manufacturing, and the honing stone is the key tool directly involved in the cutting process. It consists of three parts: abrasive, bonding agent, and porosity, and its performance directly affects machining accuracy, surface quality, and efficiency.

[0003] Existing superhard honing stones fail under prolonged use. The failure is due to the loss of grinding performance of the diamond or cubic boron nitride in the binder. There are two main reasons for this: (1) insufficient bonding between the diamond or cubic boron nitride and the metal binder, causing abrasive grains to detach during grinding; and (2) insufficient self-sharpening property of the metal binder, preventing the underlying abrasive grains from being quickly exposed after the surface abrasive grains detach, thus rendering the honing stone ineffective. To address these issues, it is necessary to perform metallization pretreatment on the abrasive grains and select a suitable metal matrix for the honing stone.

[0004] To improve the interfacial bonding performance between diamond and metal materials, some scientists have plated a layer of metal onto the surface of diamond. For example, Chinese invention patent CN102229097B, "A honing abrasive strip," pre-treats diamond abrasive grains with Ni plating. However, due to the high reactivity of Ni plating, it can easily penetrate the metal matrix of the honing stone during the sintering process, forming brittle intermetallic compounds with metals such as Cu and Sn in the metal binder. In addition, Ni plating can also cause graphitization of diamond, thereby affecting the honing performance of the honing stone.

[0005] Chinese invention patent CN103388142B, "A method for tungsten plating on diamond surface," uses tungsten powder as the tungsten source and employs a salt bath method to plating tungsten on the diamond surface in a vacuum furnace or resistance furnace. Due to the poor cleanliness of tungsten atoms during the reaction process, the pretreatment process for tungsten plating is more complex, and the cost of the tungsten source is also higher. Furthermore, it does not further sinter the tungsten-plated cubic boron nitride abrasive particles with a metal binder to prepare an ultra-hard honing oilstone, resulting in poor performance. Summary of the Invention

[0006] The purpose of this invention is to propose a honing stone with ordered abrasive grain arrangement and its manufacturing method, which overcomes the pain points of uneven abrasive grain distribution, disordered cutting load, and blocked chip removal channels in traditional randomly arranged honing stones, and improves cutting efficiency, machining quality and precision stability, thus making it suitable for more precise honing environments.

[0007] The technical solution of this invention is implemented as follows: This invention provides a method for manufacturing a honing stone with ordered abrasive grain arrangement. The method involves mixing and ball milling alloy powder, ceramic powder, silicon / tungsten diamond, polycrystalline cubic boron nitride, and ethanol, ultrasonically dispersing the mixture evenly, and hot-pressing and sintering it to obtain a matrix. The matrix is ​​then subjected to pretreatment, surface activation, electrodeposition, and post-treatment processes to obtain a honing stone with ordered abrasive grain arrangement.

[0008] As a further improvement to the present invention, the following steps are included: S1. Preparation of polycrystalline cubic boron nitride: Silicon nitride, aluminum nitride, aluminum oxide, cerium oxide and cubic boron nitride are mixed and ball-milled until uniform, sintered under pressure under inert gas protection, and cooled to room temperature to obtain polycrystalline cubic boron nitride; S2. Preparation of silicon / tungsten diamond: After ball milling, diamond abrasive is immersed in concentrated sulfuric acid, filtered, washed, and dried to obtain pretreated diamond. It is then added to a mixture of silicon powder, tungsten powder, and calcium chloride powder, mixed evenly, vacuum sintered, cooled to room temperature, sieved, washed, and dried to obtain silicon / tungsten diamond. S3. Preparation of the matrix: The alloy powder, ceramic powder, silicon / tungsten diamond, polycrystalline cubic boron nitride and ethanol are mixed and ball-milled, ultrasonically dispersed evenly, hot-pressed and sintered, and cooled to room temperature to obtain the matrix; S4. Pretreatment: The substrate is ground and polished in sequence to reduce the surface roughness of the substrate, remove rust, remove surface dirt and remove burrs and scratches, then soak in alkaline solution to remove oil, soak in acid solution to activate, take out, wash, dry, and coat the surface with electrodeposition protective paint to obtain the pretreated substrate. S5. Surface activation: The pretreated substrate is added to the electrodeposition solution for surface activation to obtain a surface-activated substrate; S6. Electrodeposition: The surface-activated substrate is coated with abrasive using the buried sand method. The abrasive used for this coating is a mixture of polycrystalline cubic boron nitride and silicon / tungsten diamond. After the coating is completed, the substrate is pulled out, washed, dried, and then buried in sand again for further electrodeposition treatment to obtain the electrodeposition substrate. S7. Post-treatment: After removing the electrodeposition protective coating from the electrodeposition substrate, immerse it in a nickel passivation solution, remove it, wash it, and perform a heat drying treatment to obtain a honing stone with ordered abrasive grain arrangement.

[0009] As a further improvement of the present invention, the mass ratio of silicon nitride, aluminum nitride, aluminum oxide, cerium oxide and cubic boron nitride in step S1 is 10-15:5-10:3-7:2-4:50-70, the pressure of the pressure sintering is 25-35 MPa, the temperature is 1300-1500℃, and the time is 15-30 min.

[0010] As a further improvement of the present invention, the average diameter of the diamond abrasive in step S2 is 10-20 μm, the ball milling time is 20-40 min, the soaking time is 20-24 h, the mass ratio of the mixed powder of silicon powder, tungsten powder and calcium chloride is 1:0.2-0.5:3-5; the mass ratio of the pretreated diamond to the mixed powder is 1:4-6; and the vacuum degree of the vacuum sintering is 1-3 × 10⁻⁶. -3 Pa, temperature 1100-1200℃, time 30-60min.

[0011] As a further improvement of the present invention, in step S3, the mass ratio of alloy powder, ceramic powder, silicon / tungsten diamond, polycrystalline cubic boron nitride, and ethanol is 3-5:5-10:2-4:20-30:30-50. The alloy powder includes copper powder, tin powder, and nickel powder in a mass ratio of 3-5:5-7:5-10. The ceramic powder includes alumina and silicon oxide in a mass ratio of 3-5:6-9. The ultrasonic power is 500-1000W, the time is 20-40min, and the hot pressing sintering pressure is 400-500MPa and the temperature is 900-1000℃.

[0012] As a further improvement of the present invention, the alkaline solution in step S4 is a 5-10 wt% NaOH or KOH solution, and the acid solution is an 8-15 wt% HCl solution.

[0013] As a further improvement of the present invention, the surface activation conditions in step S5 are: surface activation thickness 3-5 μm, current density 0.7-0.8 A / dm². 2 The current is 0.1-0.3A, and the surface activation time is 15-30 min; in step S6, the thickness of the sand coating is 5-10 μm, and the current density is 0.3-0.4 A / dm. 2 The current is 0.05-0.15A, the sand application time is 60-80 minutes, and the electrodeposition conditions are: coating thickness 30-60μm, current density 1-1.3A / dm³. 2 The current is 0.2-0.4A, and the sand application time is 120-150 minutes.

[0014] As a further improvement of the present invention, the electrodeposition solution formula is as follows: nickel aminosulfonate 250-350 g / L, nickel sulfate 10-20 g / L, 1,4-butynediol 0.1-0.3 g / L, boric acid 20-40 g / L, sodium dodecyl sulfonate 0.05-0.1 g / L, sodium saccharin 0.5-1 g / L.

[0015] As a further improvement of the present invention, the soaking time in step S7 is 2-4 minutes, and the temperature of the heating and drying treatment is 150-200°C, and the time is 2-4 hours.

[0016] The present invention further protects a honing stone with ordered abrasive grain arrangement obtained by the above-described manufacturing method.

[0017] The present invention has the following beneficial effects: The high-temperature reaction of Si3N4, AlN, and Al2O3 generates the Si4Al2O2N6 phase, forming an intergranular bridging structure that fills the gaps between cubic boron nitride particles, increasing density and inhibiting microcrack propagation. Al2O3 refines the grains and improves fracture toughness, while CeO2 acts as a sintering aid and purifier, promoting liquid-phase sintering, lowering the sintering temperature, purifying grain boundaries, and enhancing the interfacial bonding strength of the cubic boron nitride-bonded phases. This process produces a dense cubic boron nitride polycrystalline sintered body, in which the boron nitride retains its cubic structure, exhibiting extremely high strength and excellent mechanical properties.

[0018] Diamond materials have found applications in many fields due to their excellent thermophysical properties and continuously decreasing production costs. However, diamond has high interfacial energy with most metal matrices and ceramics, resulting in poor bonding between diamond particles and the matrix, and diamond particles are prone to premature detachment during use. Currently, among strong carbide elements, silicon is a semiconductor element, possessing both metallic and ceramic properties. Furthermore, silicon has superior thermal conductivity and mechanical properties compared to other elements, thus playing an effective role at the interface. Silicon in the coating reacts with carbon on the diamond surface to form silicon carbide, and tungsten reacts to form tungsten carbide. These two compounds have a high lattice matching degree with the ceramic binder, forming strong chemical bonds that replace the physical adsorption of pure diamond, thereby improving the bonding strength. The silicon / tungsten diamond abrasive and polycrystalline cubic boron nitride abrasive prepared by adding them to the matrix preparation in a certain proportion can effectively avoid the generation of pores during the sintering process and improve the yield of matrix preparation. At the same time, after the material is ball-milled and ultrasonically treated, the particle size and distribution of the matrix are more uniform, thereby achieving a more orderly arrangement of abrasive particles in the matrix.

[0019] The compatibility of the thermal expansion coefficients of ceramic binders and cubic boron nitride abrasives significantly affects the strength of the grinding wheel. Ceramic binders with lower thermal expansion coefficients and higher strength are more suitable as sintering agents for this matrix. Metal sintering agent alloy powders include copper, tin, and nickel. Their low melting point, ease of sintering, high liquid phase fluidity, ability to achieve dense filling and prevent shedding, balanced toughness and hardness for impact resistance, and high thermal conductivity to prevent burns make them the preferred binders for ultra-hard honing stones. The combination of both improves grinding wheel life and machining accuracy, reduces overall costs, and overcomes the limitations of single binders. Ceramic particles enhance the overall hardness of the binder, inhibit metal plastic deformation, provide impact resistance and prevent chipping of the metal, uniformly disperse stress, and facilitate machining, allowing the grinding wheel to adapt to more complex and demanding machining scenarios.

[0020] In the electrodeposition process, after the substrate activation treatment, a thin coating is activated on the substrate surface. This coating does not contain abrasive particles, ensuring the bonding strength between the coating and the substrate and preventing excessive internal stress. After surface activation, electrodeposition is used to initially fix a layer of abrasive particles tightly adhering to the substrate onto the activated surface layer, improving the bonding force between the two. Further, during the thickening process, the abrasive particles are completely fixed to the substrate, effectively preventing subsequent abrasive particle detachment.

[0021] This invention comprises three main aspects: First, a superhard polycrystalline component formulation (including silicon / tungsten diamond and polycrystalline cubic boron nitride) employs a rich blend of metal and ceramic binders to obtain binders with higher activity and purity, thereby improving the bonding quality of cubic boron nitride. Second, a high-temperature, high-pressure synthesis process, combined with ultrasonic technology, effectively solves the challenges of separating ultrafine powders with particle sizes of 5μm and below and achieving ordered arrangement of dispersed abrasive particles. Furthermore, by controlling the generation of the polycrystalline cubic boron nitride mesophase and its bonding behavior with cubic boron nitride, high-quality polycrystalline diamond synthesis is achieved, reducing performance changes caused by closed pores and obtaining a matrix material with high uniformity, high strength, low porosity, and high yield. Third, a deformation reduction technology is implemented by adding silicon / tungsten diamond to the two binders to prevent uneven firing shrinkage due to inconsistent expansion coefficients, thus avoiding defects such as bending deformation, cracks, and delamination. Fourth, the present invention uses an electrodeposition method to deposit abrasive on the surface layer of the substrate. Under the action of an electric field, the abrasive can be arranged in an orderly manner on the surface of the honing stone, which overcomes the pain points of uneven abrasive distribution, disordered cutting load, and blockage of chip removal channels in traditional randomly arranged honing stones, and improves cutting efficiency, processing quality and precision stability, thus making it suitable for more precise honing environments.

[0022] The product of this invention is mainly used for machining precision, complex and hard metal workpieces such as automobile engine blocks, hydraulic cylinders, and bearing rings. It has taken the lead in replacing imported honing stones in the oil pump and nozzle industry, realizing the domestic substitution of honing stones. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a photograph of the honing stone with ordered abrasive grain arrangement prepared in Example 1. Detailed Implementation

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] Diamond abrasive has an average diameter of 10-20 μm.

[0027] Example 1 This embodiment provides a method for manufacturing a honing stone with ordered abrasive grain arrangement, including the following steps: S1. Preparation of polycrystalline cubic boron nitride: 10g silicon nitride, 5g aluminum nitride, 3g aluminum oxide, 2g cerium oxide and 50g cubic boron nitride were mixed and ball-milled for 2h. Under nitrogen protection, the pressure was 25MPa and the temperature was 1300℃. The mixture was then sintered for 15min under pressure and cooled to room temperature to obtain polycrystalline cubic boron nitride. S2. Preparation of silicon / tungsten-plated diamond: Diamond abrasive is ball-milled for 20 min, then immersed in concentrated sulfuric acid for 20 h, filtered, washed, and dried to obtain pretreated diamond. This pretreated diamond is then added to a mixture of silicon powder, tungsten powder, and calcium chloride powder, with a mass ratio of 1:0.2:3. The mass ratio of the pretreated diamond to the mixed powder is 1:4. The mixture is thoroughly mixed and then vacuum-sintered at a vacuum degree of 1×10⁻⁶. -3 Pa, temperature 1100℃, time 30min, cool to room temperature, sieve, wash, dry, to obtain silicon / tungsten diamond; S3. Preparation of the matrix: 3g alloy powder, 5g ceramic powder, 2g silicon / tungsten diamond, 20g polycrystalline cubic boron nitride and 30g ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 500W for 20min, hot-pressed and sintered at 400MPa, 900℃ for 1h, and cooled to room temperature to obtain the matrix; The alloy powder includes copper powder, tin powder and nickel powder in a mass ratio of 3:5:5, and the ceramic powder includes alumina and silicon oxide in a mass ratio of 3:6. S4. Pretreatment: The substrate is ground and polished in sequence, then immersed in 5wt% NaOH solution for 20 min, and then immersed in 8wt% HCl solution for 2 min. After removal, washing, drying, and coating the surface with electrodeposition protective paint, the pretreated substrate is obtained. S5. Surface activation: The pretreated substrate is added to the electrodeposition solution for surface activation to obtain a surface-activated substrate; Surface activation conditions: surface activation thickness 3 μm, current density 0.7 A / dm² 2 The current was 0.1A, and the surface activation time was 15min. Electrodeposition solution formulation: Nickel sulfamate 250 g / L, nickel sulfate 10 g / L, 1,4-butynediol 0.1 g / L, boric acid 20 g / L, sodium dodecyl sulfate 0.05 g / L, sodium saccharin 0.5 g / L.

[0028] S6. Electrodeposition: A sand-coating method is used to coat the surface-activated substrate with sand, with a sand thickness of 5 μm and a current density of 0.3 A / dm. 2 The current was 0.05A, and the abrasive application time was 60 minutes. The abrasive used was a mixture of polycrystalline cubic boron nitride and silicon / tungsten diamond in a mass ratio of 30:5. After abrasive application, the substrate was removed, washed, dried, and then buried in abrasive again for electrodeposition. The electrodeposition conditions were: coating thickness of 30μm and current density of 1A / dm³. 2 The current was 0.2A, the sand application time was 120min, and the electrodeposition substrate was obtained. Electrodeposition solution formulation: Nickel sulfamate 250 g / L, nickel sulfate 10 g / L, 1,4-butynediol 0.1 g / L, boric acid 20 g / L, sodium dodecyl sulfate 0.05 g / L, sodium saccharin 0.5 g / L.

[0029] S7. Post-treatment: After removing the electrodeposited protective coating from the electrodeposited substrate, immerse it in a nickel passivation solution for 2 minutes, remove it, wash it, heat it to 150℃, and dry it for 2 hours to obtain a honing stone with ordered abrasive grain arrangement. A photograph of this honing stone is shown below. Figure 1 .

[0030] Example 2 This embodiment provides a method for manufacturing a honing stone with ordered abrasive grain arrangement, including the following steps: S1. Preparation of polycrystalline cubic boron nitride: 15g silicon nitride, 10g aluminum nitride, 7g aluminum oxide, 4g cerium oxide and 70g cubic boron nitride were mixed and ball-milled for 2h. Under nitrogen protection, the mixture was sintered at a pressure of 35MPa and a temperature of 1500℃ for 30min and then cooled to room temperature to obtain polycrystalline cubic boron nitride. S2. Preparation of silicon / tungsten coated diamond: Diamond abrasive was ball-milled for 40 min, then immersed in concentrated sulfuric acid for 24 h, filtered, washed, and dried to obtain pretreated diamond. This pretreated diamond was then added to a mixture of silicon powder, tungsten powder, and calcium chloride powder, with a mass ratio of 1:0.5:5. The mass ratio of the pretreated diamond to the mixed powder was 1:6. The mixture was thoroughly mixed and then vacuum sintered at a vacuum degree of 3 × 10⁻⁶. -3 Pa, temperature 1200℃, time 60min, cool to room temperature, sieve, wash, dry, to obtain silicon / tungsten diamond; S3. Preparation of the matrix: 5g alloy powder, 10g ceramic powder, 4g silicon / tungsten diamond, 30g polycrystalline cubic boron nitride and 50g ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 1000W for 40min, hot-pressed and sintered at 500MPa and 1000℃ for 1h, and cooled to room temperature to obtain the matrix; The alloy powder includes copper powder, tin powder and nickel powder in a mass ratio of 5:7:10, and the ceramic powder includes alumina and silicon oxide in a mass ratio of 5:9. S4. Pretreatment: The substrate is ground and polished in sequence, then immersed in 10wt% KOH solution for 20min, and then immersed in 15wt% HCl solution for 2min. After removal, washing and drying, the surface is coated with electrodeposition protective paint to obtain the pretreated substrate. S5. Surface activation: The pretreated substrate is added to the electrodeposition solution for surface activation to obtain a surface-activated substrate; Surface activation conditions: surface activation thickness 5 μm, current density 0.8 A / dm² 2 The current was 0.3A and the surface activation time was 30min. Electrodeposition solution formulation: Nickel sulfamate 2350 g / L, nickel sulfate 20 g / L, 1,4-butynediol 0.3 g / L, boric acid 40 g / L, sodium dodecyl sulfate 0.1 g / L, sodium saccharin 1 g / L.

[0031] S6. Electrodeposition: A sand-coating method is used to coat the surface-activated substrate with sand, with a sand thickness of 10 μm and a current density of 0.4 A / dm. 2 The current was 0.15A, and the abrasive application time was 80 minutes. The abrasive used was a mixture of polycrystalline cubic boron nitride and silicon / tungsten diamond in a mass ratio of 30:5. After abrasive application, the substrate was removed, washed, dried, and then re-embedded in abrasive for electrodeposition. The electrodeposition conditions were: a coating thickness of 60 μm and a current density of 1.3 A / dm². 2 The current was 0.4A, the sand application time was 150min, and the electrodeposition substrate was obtained. Electrodeposition solution formulation: Nickel aminosulfonate 350 g / L, nickel sulfate 20 g / L, 1,4-butynediol 0.3 g / L, boric acid 40 g / L, sodium dodecyl sulfate 0.1 g / L, sodium saccharin 1 g / L.

[0032] S7. Post-treatment: After removing the electrodeposition protective coating from the electrodeposition substrate, immerse it in a nickel passivation solution for 4 minutes, remove it, wash it, heat it to 200℃, and dry it for 4 hours to obtain a honing stone with ordered abrasive grain arrangement.

[0033] Example 3 This embodiment provides a method for manufacturing a honing stone with ordered abrasive grain arrangement, including the following steps: S1. Preparation of polycrystalline cubic boron nitride: 12g silicon nitride, 7g aluminum nitride, 5g aluminum oxide, 3g cerium oxide and 60g cubic boron nitride were mixed and ball-milled for 2h. Under nitrogen protection, the mixture was sintered at a pressure of 30MPa and a temperature of 1400℃ for 22min and then cooled to room temperature to obtain polycrystalline cubic boron nitride. S2. Preparation of silicon / tungsten-plated diamond: Diamond abrasive was ball-milled for 30 min, then immersed in concentrated sulfuric acid for 22 h, filtered, washed, and dried to obtain pretreated diamond. This pretreated diamond was then added to a mixture of silicon powder, tungsten powder, and calcium chloride powder, with a mass ratio of 1:0.35:4. The mass ratio of the pretreated diamond to the mixed powder was 1:5. The mixture was thoroughly mixed and then vacuum-sintered at a vacuum degree of 2 × 10⁻⁶. -3 Pa, temperature 1150℃, time 45min, cool to room temperature, sieve, wash, dry, to obtain silicon / tungsten diamond; S3. Preparation of the matrix: 4g alloy powder, 7g ceramic powder, 3g silicon / tungsten diamond, 25g polycrystalline cubic boron nitride and 40g ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 700W for 30min, hot-pressed and sintered at 450MPa, 950℃ for 1h, and cooled to room temperature to obtain the matrix. The alloy powder includes copper powder, tin powder and nickel powder in a mass ratio of 4:6:8, and the ceramic powder includes alumina and silicon oxide in a mass ratio of 4:7. S4. Pretreatment: The substrate is ground and polished in sequence, then immersed in 8wt% NaOH solution for 20 min, and then immersed in 10wt% HCl solution for 2 min. After removal, washing and drying, the surface is coated with electrodeposition protective paint to obtain the pretreated substrate. S5. Surface activation: The pretreated substrate is added to the electrodeposition solution for surface activation to obtain a surface-activated substrate; Surface activation conditions: Surface activation thickness 4 μm, current density 0.75 A / dm² 2The current was 0.2A, and the surface activation time was 20min. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0034] S6. Electrodeposition: A sand-coating method is used to coat the surface-activated substrate with sand, with a sand thickness of 7 μm and a current density of 0.35 A / dm. 2 The current was 0.1A, and the abrasive application time was 70 minutes. The abrasive used was a mixture of polycrystalline cubic boron nitride and silicon / tungsten diamond in a mass ratio of 30:5. After abrasive application, the substrate was removed, washed, dried, and then re-immersed in abrasive for electrodeposition. The electrodeposition conditions were: coating thickness 45μm, current density 1.15A / dm³. 2 The current was 0.3A, the sand application time was 135min, and the electrodeposition substrate was obtained. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0035] S7. Post-treatment: After removing the electrodeposition protective coating from the electrodeposition substrate, immerse it in a nickel passivation solution for 3 minutes, remove it, wash it, heat it to 170°C, and dry it for 3 hours to obtain a honing stone with ordered abrasive grain arrangement.

[0036] Comparative Example 1 The difference from Example 3 is that the polycrystalline cubic boron nitride is replaced by an equal mass of cubic boron nitride.

[0037] Comparative Example 2 The difference from Example 3 is that tungsten powder was not added in step S2.

[0038] Specifically as follows: S1. Preparation of polycrystalline cubic boron nitride: 12g silicon nitride, 7g aluminum nitride, 5g aluminum oxide, 3g cerium oxide and 60g cubic boron nitride were mixed and ball-milled for 2h. Under nitrogen protection, the mixture was sintered at a pressure of 30MPa and a temperature of 1400℃ for 22min and then cooled to room temperature to obtain polycrystalline cubic boron nitride. S2. Preparation of silicon-coated diamond: Diamond abrasive was ball-milled for 30 minutes, then immersed in concentrated sulfuric acid for 22 hours. After filtration, washing, and drying, pretreated diamond was obtained. This pretreated diamond was then added to a mixture of silicon powder and calcium chloride powder at a mass ratio of 1.35:4; the mass ratio of the pretreated diamond to the mixed powder was 1:5. The mixture was thoroughly mixed and then vacuum-sintered at a vacuum degree of 2 × 10⁻⁶. -3 Pa, temperature 1150℃, time 45min, cool to room temperature, sieve, wash, dry to obtain silicon-coated diamond; S3. Preparation of the matrix: 4g alloy powder, 7g ceramic powder, 3g silicon / tungsten diamond, 25g polycrystalline cubic boron nitride and 40g ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 700W for 30min, hot-pressed and sintered at 450MPa, 950℃ for 1h, and cooled to room temperature to obtain the matrix. The alloy powder includes copper powder, tin powder and nickel powder in a mass ratio of 4:6:8, and the ceramic powder includes alumina and silicon oxide in a mass ratio of 4:7. S4. Pretreatment: The substrate is ground and polished in sequence, then immersed in 8wt% NaOH solution for 20 min, and then immersed in 10wt% HCl solution for 2 min. After removal, washing and drying, the surface is coated with electrodeposition protective paint to obtain the pretreated substrate. S5. Surface activation: The pretreated substrate is added to the electrodeposition solution for surface activation to obtain a surface-activated substrate; Surface activation conditions: Surface activation thickness 4 μm, current density 0.75 A / dm² 2 The current was 0.2A, and the surface activation time was 20min. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0039] S6. Electrodeposition: A sand-coating method is used to coat the surface-activated substrate with sand, with a sand thickness of 7 μm and a current density of 0.35 A / dm. 2 The current was 0.1A, and the abrasive application time was 70 minutes. The abrasive used was a mixture of polycrystalline cubic boron nitride and silicon / tungsten diamond in a mass ratio of 30:5. After abrasive application, the substrate was removed, washed, dried, and then re-immersed in abrasive for electrodeposition. The electrodeposition conditions were: coating thickness 45μm, current density 1.15A / dm³. 2 The current was 0.3A, the sand application time was 135min, and the electrodeposition substrate was obtained. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0040] S7. Post-treatment: After removing the electrodeposition protective coating from the electrodeposition substrate, immerse it in a nickel passivation solution for 3 minutes, remove it, wash it, heat it to 170°C, and dry it for 3 hours to obtain a honing stone with ordered abrasive grain arrangement.

[0041] Comparative Example 3 The difference from Example 3 is that no silicon powder was added in step S2.

[0042] Specifically as follows: S1. Preparation of polycrystalline cubic boron nitride: 12g silicon nitride, 7g aluminum nitride, 5g aluminum oxide, 3g cerium oxide and 60g cubic boron nitride were mixed and ball-milled for 2h. Under nitrogen protection, the mixture was sintered at a pressure of 30MPa and a temperature of 1400℃ for 22min and then cooled to room temperature to obtain polycrystalline cubic boron nitride. S2. Preparation of tungsten-plated diamond: Diamond abrasive was ball-milled for 30 minutes, then immersed in concentrated sulfuric acid for 22 hours. After filtration, washing, and drying, pretreated diamond was obtained. This pretreated diamond was then added to a mixture of tungsten powder and calcium chloride powder at a mass ratio of 35:4; the mass ratio of the pretreated diamond to the mixed powder was 1:5. The mixture was thoroughly mixed and then vacuum-sintered at a vacuum degree of 2 × 10⁻⁶. -3 Pa, temperature 1150℃, time 45min, cool to room temperature, sieve, wash, dry to obtain tungsten-plated diamond; S3. Preparation of the matrix: 4g alloy powder, 7g ceramic powder, 3g silicon / tungsten diamond, 25g polycrystalline cubic boron nitride and 40g ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 700W for 30min, hot-pressed and sintered at 450MPa, 950℃ for 1h, and cooled to room temperature to obtain the matrix. The alloy powder includes copper powder, tin powder and nickel powder in a mass ratio of 4:6:8, and the ceramic powder includes alumina and silicon oxide in a mass ratio of 4:7. S4. Pretreatment: The substrate is ground and polished in sequence, then immersed in 8wt% NaOH solution for 20 min, and then immersed in 10wt% HCl solution for 2 min. After removal, washing and drying, the surface is coated with electrodeposition protective paint to obtain the pretreated substrate. S5. Surface activation: The pretreated substrate is added to the electrodeposition solution for surface activation to obtain a surface-activated substrate; Surface activation conditions: Surface activation thickness 4 μm, current density 0.75 A / dm² 2The current was 0.2A, and the surface activation time was 20min. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0043] S6. Electrodeposition: A sand-coating method is used to coat the surface-activated substrate with sand, with a sand thickness of 7 μm and a current density of 0.35 A / dm. 2 The current was 0.1A, and the abrasive application time was 70 minutes. The abrasive used was a mixture of polycrystalline cubic boron nitride and silicon / tungsten diamond in a mass ratio of 30:5. After abrasive application, the substrate was removed, washed, dried, and then re-immersed in abrasive for electrodeposition. The electrodeposition conditions were: coating thickness 45μm, current density 1.15A / dm³. 2 The current was 0.3A, the sand application time was 135min, and the electrodeposition substrate was obtained. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0044] S7. Post-treatment: After removing the electrodeposition protective coating from the electrodeposition substrate, immerse it in a nickel passivation solution for 3 minutes, remove it, wash it, heat it to 170°C, and dry it for 3 hours to obtain a honing stone with ordered abrasive grain arrangement.

[0045] Comparative Example 4 The difference from Example 3 is that step S2 was not performed.

[0046] Specifically as follows: S1. Preparation of polycrystalline cubic boron nitride: 12g silicon nitride, 7g aluminum nitride, 5g aluminum oxide, 3g cerium oxide and 60g cubic boron nitride were mixed and ball-milled for 2h. Under nitrogen protection, the mixture was sintered at a pressure of 30MPa and a temperature of 1400℃ for 22min and then cooled to room temperature to obtain polycrystalline cubic boron nitride. S2. Preparation of the matrix: 4g alloy powder, 7g ceramic powder, 3g diamond abrasive, 25g polycrystalline cubic boron nitride and 40g ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 700W for 30min, hot-pressed and sintered at 450MPa, 950℃ for 1h, and cooled to room temperature to obtain the matrix. The alloy powder includes copper powder, tin powder and nickel powder in a mass ratio of 4:6:8, and the ceramic powder includes alumina and silicon oxide in a mass ratio of 4:7. S3. Pretreatment: The substrate is ground and polished in sequence, then immersed in 8wt% NaOH solution for 20 min, and then immersed in 10wt% HCl solution for 2 min. After removal, washing and drying, the surface is coated with electrodeposition protective paint to obtain the pretreated substrate. S4. Surface activation: The pretreated substrate is added to the electrodeposition solution for surface activation to obtain a surface-activated substrate; Surface activation conditions: Surface activation thickness 4 μm, current density 0.75 A / dm² 2 The current was 0.2A, and the surface activation time was 20min. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0047] S5. Electrodeposition: A sand-coating method is used to coat the surface-activated substrate with sand, with a sand thickness of 7 μm and a current density of 0.35 A / dm. 2 The current was 0.1A, and the abrasive application time was 70 minutes. The abrasive used was a mixture of polycrystalline cubic boron nitride and silicon / tungsten diamond in a mass ratio of 30:5. After abrasive application, the substrate was removed, washed, dried, and then re-immersed in abrasive for electrodeposition. The electrodeposition conditions were: coating thickness 45μm, current density 1.15A / dm³. 2 The current was 0.3A, the sand application time was 135min, and the electrodeposition substrate was obtained. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0048] S6. Post-treatment: After removing the electrodeposition protective coating from the electrodeposition substrate, immerse it in a nickel passivation solution for 3 minutes, remove it, wash it, heat it to 170°C, and dry it for 3 hours to obtain a honing stone with ordered abrasive grain arrangement.

[0049] Comparative Example 5 The difference from Example 3 is that silicon / tungsten diamond was not added in step S3.

[0050] Specifically as follows: S1. Preparation of polycrystalline cubic boron nitride: 12g silicon nitride, 7g aluminum nitride, 5g aluminum oxide, 3g cerium oxide and 60g cubic boron nitride were mixed and ball-milled for 2h. Under nitrogen protection, the mixture was sintered at a pressure of 30MPa and a temperature of 1400℃ for 22min and then cooled to room temperature to obtain polycrystalline cubic boron nitride. S2. Preparation of the matrix: 4g of alloy powder, 7g of ceramic powder, 28g of polycrystalline cubic boron nitride and 40g of ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 700W for 30min, hot-pressed and sintered at a pressure of 450MPa, a temperature of 950℃ and a time of 1h, and cooled to room temperature to obtain the matrix. The alloy powder includes copper powder, tin powder and nickel powder in a mass ratio of 4:6:8, and the ceramic powder includes alumina and silicon oxide in a mass ratio of 4:7. S3. Pretreatment: The substrate is ground and polished in sequence, then immersed in 8wt% NaOH solution for 20 min, and then immersed in 10wt% HCl solution for 2 min. After removal, washing and drying, the surface is coated with electrodeposition protective paint to obtain the pretreated substrate. S4. Surface activation: The pretreated substrate is added to the electrodeposition solution for surface activation to obtain a surface-activated substrate; Surface activation conditions: Surface activation thickness 4 μm, current density 0.75 A / dm² 2 The current was 0.2A, and the surface activation time was 20min. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0051] S5. Electrodeposition: A sand-coating method is used to coat the surface-activated substrate with sand, with a sand thickness of 7 μm and a current density of 0.35 A / dm. 2 The current was 0.1A, and the abrasive application time was 70 minutes. The abrasive used was a mixture of polycrystalline cubic boron nitride and silicon / tungsten diamond in a mass ratio of 30:5. After abrasive application, the substrate was removed, washed, dried, and then re-immersed in abrasive for electrodeposition. The electrodeposition conditions were: coating thickness 45μm, current density 1.15A / dm³. 2 The current was 0.3A, the sand application time was 135min, and the electrodeposition substrate was obtained. Electrodeposition solution formulation: Nickel aminosulfonate 300 g / L, nickel sulfate 15 g / L, 1,4-butynediol 0.2 g / L, boric acid 30 g / L, sodium dodecyl sulfate 0.07 g / L, sodium saccharin 0.7 g / L.

[0052] S6. Post-treatment: After removing the electrodeposition protective coating from the electrodeposition substrate, immerse it in a nickel passivation solution for 3 minutes, remove it, wash it, heat it to 170°C, and dry it for 3 hours to obtain a honing stone with ordered abrasive grain arrangement.

[0053] Comparative Example 6 The difference from Example 3 is that steps S4 to S7 were not performed.

[0054] Specifically as follows: S1. Preparation of polycrystalline cubic boron nitride: 12g silicon nitride, 7g aluminum nitride, 5g aluminum oxide, 3g cerium oxide and 60g cubic boron nitride were mixed and ball-milled for 2h. Under nitrogen protection, the mixture was sintered at a pressure of 30MPa and a temperature of 1400℃ for 22min and then cooled to room temperature to obtain polycrystalline cubic boron nitride. S2. Preparation of silicon / tungsten-plated diamond: Diamond abrasive was ball-milled for 30 min, then immersed in concentrated sulfuric acid for 22 h, filtered, washed, and dried to obtain pretreated diamond. This pretreated diamond was then added to a mixture of silicon powder, tungsten powder, and calcium chloride powder, with a mass ratio of 1:0.35:4. The mass ratio of the pretreated diamond to the mixed powder was 1:5. The mixture was thoroughly mixed and then vacuum-sintered at a vacuum degree of 2 × 10⁻⁶. -3 Pa, temperature 1150℃, time 45min, cool to room temperature, sieve, wash, dry, to obtain silicon / tungsten diamond; S3. Preparation of the matrix: 4g alloy powder, 7g ceramic powder, 3g silicon / tungsten diamond, 25g polycrystalline cubic boron nitride and 40g ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 700W for 30min, hot-pressed and sintered at 450MPa, 950℃ for 1h, and cooled to room temperature to obtain a honing stone with ordered abrasive grain arrangement; The alloy powder comprises copper powder, tin powder, and nickel powder in a mass ratio of 4:6:8, and the ceramic powder comprises alumina and silicon oxide in a mass ratio of 4:7.

[0055] Comparative Example 7 Compared with Example 3, the difference is that ultrasonic treatment was not performed in step S3, and steps S4 to S7 were not performed.

[0056] Specifically as follows: S1. Preparation of polycrystalline cubic boron nitride: 12g silicon nitride, 7g aluminum nitride, 5g aluminum oxide, 3g cerium oxide and 60g cubic boron nitride were mixed and ball-milled for 2h. Under nitrogen protection, the mixture was sintered at a pressure of 30MPa and a temperature of 1400℃ for 22min and then cooled to room temperature to obtain polycrystalline cubic boron nitride. S2. Preparation of silicon / tungsten-plated diamond: Diamond abrasive was ball-milled for 30 min, then immersed in concentrated sulfuric acid for 22 h, filtered, washed, and dried to obtain pretreated diamond. This pretreated diamond was then added to a mixture of silicon powder, tungsten powder, and calcium chloride powder, with a mass ratio of 1:0.35:4. The mass ratio of the pretreated diamond to the mixed powder was 1:5. The mixture was thoroughly mixed and then vacuum-sintered at a vacuum degree of 2 × 10⁻⁶. -3Pa, temperature 1150℃, time 45min, cool to room temperature, sieve, wash, dry, to obtain silicon / tungsten diamond; S3. Preparation of the matrix: 4g alloy powder, 7g ceramic powder, 3g silicon / tungsten diamond, 25g polycrystalline cubic boron nitride and 40g ethanol were mixed and ball-milled for 1h, hot-pressed and sintered at a pressure of 450MPa, a temperature of 950℃ and a time of 1h, and cooled to room temperature to obtain honing oilstone. The alloy powder comprises copper powder, tin powder, and nickel powder in a mass ratio of 4:6:8, and the ceramic powder comprises alumina and silicon oxide in a mass ratio of 4:7.

[0057] Comparative Example 8 The difference from Example 3 is that no alloy powder was added in step S3.

[0058] Specifically as follows: S3. Preparation of the matrix: 11g of ceramic powder, 3g of silicon / tungsten diamond, 25g of polycrystalline cubic boron nitride and 40g of ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 700W for 30min, hot-pressed and sintered at 450MPa, 950℃ for 1h, and cooled to room temperature to obtain the matrix. The ceramic powder comprises alumina and silicon oxide in a mass ratio of 4:7.

[0059] Comparative Example 9 The difference from Example 3 is that ceramic powder was not added in step S3.

[0060] Specifically as follows: S3. Preparation of the matrix: 11g of alloy powder, 3g of silicon / tungsten diamond, 25g of polycrystalline cubic boron nitride and 40g of ethanol were mixed and ball-milled for 1h, ultrasonically dispersed at 700W for 30min, hot-pressed and sintered at a pressure of 450MPa, a temperature of 950℃ and a time of 1h, and cooled to room temperature to obtain the matrix. The alloy powder comprises copper powder, tin powder, and nickel powder in a mass ratio of 4:6:8.

[0061] Test Example 1 The matrices prepared in Examples 1-3, Comparative Examples 1-5, and Comparative Examples 7-9 were subjected to performance tests, and the results are shown in Table 1.

[0062] Wear resistance: The wear resistance of the samples was characterized by the wear ratio using a UMT-2 friction and wear testing machine. The wear ratio is the ratio of the volume lost by the specimen to the volume lost by the ground specimen, which reflects the strength of the specimen's machinability. The smaller the value, the stronger the specimen's machinability.

[0063] Bending strength: Tested using a DDL-100 universal testing machine. The result is the bending strength. The larger the value, the greater the bending strength of the specimen.

[0064] Table 1

[0065] As can be seen from the table above, the matrix prepared in Examples 1-3 of the present invention has good wear resistance and bending strength.

[0066] Test Example 2 The honing stones prepared in Examples 1-3 and Comparative Examples 1-9 were compared with those used in the market to process the same hydraulic cylinder barrel (45 steel / cylinder diameter 210mm), with 8 honing stones evenly embedded in each honing head. The results are shown in Table 2.

[0067] Table 2

[0068] As can be seen from the table above, the honing stones prepared in Examples 1-3 of the present invention have finer processing and higher surface finish.

[0069] In Comparative Example 1, the polycrystalline cubic boron nitride was replaced by an equal mass of cubic boron nitride, resulting in a decrease in its wear ratio and flexural strength. The high-temperature reaction of Si3N4, AlN, and Al2O3 generates the Si4Al2O2N6 phase, forming an intergranular bridging structure that fills the gaps between cubic boron nitride particles, increasing density and inhibiting microcrack propagation. Al2O3 refines the grains and improves fracture toughness. CeO2, acting as a sintering aid and purifier, promotes liquid-phase sintering, lowers the sintering temperature, purifies grain boundaries, and enhances the interfacial bonding strength between the cubic boron nitride and the phase, thus preparing a dense polycrystalline cubic boron nitride sintered body. The boron nitride retains its cubic structure, exhibiting extremely high strength and excellent mechanical properties.

[0070] In Comparative Examples 2 and 3, no tungsten powder or silicon powder was added in step S2; in Comparative Example 4, step S2 was not performed; and in Comparative Example 5, no silicon / tungsten-plated diamond was added in step S3. The wear ratio, bending strength, processing accuracy, and service life all decreased. Diamond materials are used in many fields due to their excellent thermophysical properties and continuously decreasing production costs. However, diamond has a high interfacial energy with most metal matrices and ceramics, resulting in poor bonding between diamond particles and the matrix, and diamond particles are prone to premature detachment during use. Currently, among strong carbide elements, silicon is a semiconductor element, possessing both metallic and ceramic properties. Furthermore, silicon has better thermal conductivity and mechanical properties than other elements, thus playing an effective role at the interface. Silicon in the coating reacts with carbon on the diamond surface to form silicon carbide, and tungsten forms tungsten carbide. These two compounds have a high lattice matching degree with the ceramic binder, forming strong chemical bonds that replace the physical adsorption of pure diamond, thereby improving the bonding strength. The silicon / tungsten diamond abrasive and polycrystalline cubic boron nitride abrasive prepared by adding them to the matrix preparation in a certain proportion can effectively avoid the generation of pores during the sintering process and improve the yield of matrix preparation. At the same time, after the material is ball-milled and ultrasonically treated, the particle size and distribution of the matrix are more uniform, thereby achieving a more orderly arrangement of abrasive particles in the matrix.

[0071] In Comparative Example 6, steps S4 to S7 resulted in a decrease in surface roughness and machining accuracy. During the electrodeposition process, after the substrate activation treatment, a thin coating was activated on the substrate surface. This coating, free of abrasive particles, ensured the bonding strength between the coating and the substrate, preventing excessive internal stress. By using electrodeposition to deposit abrasive particles onto the substrate surface, under the influence of an electric field, the abrasive particles can achieve an ordered distribution on the surface of the honing stone. This overcomes the pain points of traditional randomly distributed honing stones, such as uneven abrasive particle distribution, disordered cutting load, and blocked chip removal channels, thus improving cutting efficiency, machining quality, and precision stability, making it suitable for more precise honing environments.

[0072] In Comparative Example 7, where ultrasonic treatment was not performed in step S3 and steps S4 to S7 were not carried out, the surface roughness decreased, the machining accuracy decreased, and the wear ratio of the matrix decreased. This is because the ultrasonic treatment of the material by ball milling makes the particle size and distribution of the matrix more uniform, thereby achieving a more ordered arrangement of abrasive particles within the matrix.

[0073] Comparative Examples 8 and 9, using only ceramic powder or alloy powder, resulted in decreased processing accuracy, mechanical strength, and service life. The matching of the thermal expansion coefficients of the ceramic binder and the cubic boron nitride abrasive has a significant impact on the strength of the grinding wheel. Ceramic binders with lower thermal expansion coefficients and higher strength are more suitable as one of the sintering agents for this matrix preparation. Metal sintering agent alloy powders include copper, tin, and nickel metals. Low melting point, easy sintering, high liquid phase fluidity, achieving dense filling and preventing shedding, toughness-hardness balance and impact resistance, and high thermal conductivity to prevent burns make them the preferred binders for ultra-hard honing oilstones. The combination of both improves grinding wheel life and processing accuracy, reduces overall costs, and overcomes the application limitations of single binders. Ceramic particles increase the overall hardness of the binder, inhibit metal plastic deformation, make the metal material impact-resistant and prevent cracking, uniformly disperse stress, and are easy to process and shape, allowing the grinding wheel to adapt to more complex and demanding processing scenarios.

[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for manufacturing a honing stone with ordered abrasive grain arrangement, characterized in that, Includes the following steps: S1. Preparation of polycrystalline cubic boron nitride: Silicon nitride, aluminum nitride, aluminum oxide, cerium oxide and cubic boron nitride are mixed and ball-milled until uniform, sintered under pressure under inert gas protection, and cooled to room temperature to obtain polycrystalline cubic boron nitride; S2. Preparation of silicon / tungsten diamond: After ball milling, diamond abrasive is immersed in concentrated sulfuric acid, filtered, washed, and dried to obtain pretreated diamond. It is then added to a mixture of silicon powder, tungsten powder, and calcium chloride powder, mixed evenly, vacuum sintered, cooled to room temperature, sieved, washed, and dried to obtain silicon / tungsten diamond. S3. Preparation of the matrix: The alloy powder, ceramic powder, silicon / tungsten diamond, polycrystalline cubic boron nitride and ethanol are mixed and ball-milled, ultrasonically dispersed evenly, hot-pressed and sintered, and cooled to room temperature to obtain the matrix; S4. Pretreatment: The substrate is ground and polished in sequence to reduce the surface roughness of the substrate, remove rust, remove surface dirt and remove burrs and scratches, then soak in alkaline solution to remove oil, soak in acid solution to activate, take out, wash, dry, and coat the surface with electrodeposition protective paint to obtain the pretreated substrate. S5. Surface activation: The pretreated substrate is added to the electrodeposition solution for surface activation to obtain a surface-activated substrate; S6. Electrodeposition: The surface-activated substrate is coated with abrasive using the buried sand method. The abrasive used for this coating is a mixture of polycrystalline cubic boron nitride and silicon / tungsten diamond. After the coating is completed, the substrate is pulled out, washed, dried, and then buried in sand again for further electrodeposition treatment to obtain the electrodeposition substrate. S7. Post-treatment: After removing the electrodeposition protective coating from the electrodeposition substrate, immerse it in a nickel passivation solution, remove it, wash it, and perform a heat drying treatment to obtain a honing stone with ordered abrasive grain arrangement.

2. The manufacturing method according to claim 1, characterized in that, In step S1, the mass ratio of silicon nitride, aluminum nitride, aluminum oxide, cerium oxide, and cubic boron nitride is 10-15:5-10:3-7:2-4:50-70. The pressure of the pressure sintering is 25-35 MPa, the temperature is 1300-1500℃, and the time is 15-30 min.

3. The manufacturing method according to claim 1, characterized in that, In step S2, the average diameter of the diamond abrasive is 10-20 μm, the ball milling time is 20-40 min, the soaking time is 20-24 h, the mass ratio of the mixed powder of silicon powder, tungsten powder and calcium chloride is 1:0.2-0.5:3-5, the mass ratio of the pretreated diamond to the mixed powder is 1:4-6, the vacuum degree of the vacuum sintering is 1-3×10-3 Pa, the temperature is 1100-1200℃, and the time is 30-60 min.

4. The manufacturing method according to claim 1, characterized in that, In step S3, the mass ratio of the alloy powder, ceramic powder, silicon / tungsten diamond plating, polycrystalline cubic boron nitride, and ethanol is 3-5:5-10:2-4:20-30:30-50. The alloy powder includes copper powder, tin powder, and nickel powder in a mass ratio of 3-5:5-7:5-10. The ceramic powder includes alumina and silicon oxide in a mass ratio of 3-5:6-9. The ultrasonic power is 500-1000W, the time is 20-40min, and the hot pressing sintering pressure is 400-500MPa and the temperature is 900-1000℃.

5. The manufacturing method according to claim 1, characterized in that, The alkaline solution in step S4 is a 5-10 wt% NaOH or KOH solution, and the acid solution is an 8-15 wt% HCl solution.

6. The manufacturing method according to claim 1, characterized in that, The surface activation conditions in step S5 are: surface activation thickness 3-5 μm, current density 0.7-0.8 A / dm2, current magnitude 0.1-0.3 A, and surface activation time 15-30 min; the sand coating thickness in step S6 is 5-10 μm, current density is 0.3-0.4 A / dm2, current magnitude is 0.05-0.15 A, and sand coating time is 60-80 min; the electrodeposition conditions are: coating thickness 30-60 μm, current density is 1-1.3 A / dm2, current magnitude is 0.2-0.4 A, and sand coating time is 120-150 min.

7. The manufacturing method according to claim 6, characterized in that, Electrodeposition solution formulation: Nickel sulfamate 250-350 g / L, nickel sulfate 10-20 g / L, 1,4-butynediol 0.1-0.3 g / L, boric acid 20-40 g / L, sodium dodecyl sulfonate 0.05-0.1 g / L, sodium saccharin 0.5-1 g / L.

8. The manufacturing method according to claim 1, characterized in that, In step S7, the soaking time is 2-4 minutes, and the heating and drying treatment is carried out at a temperature of 150-200℃ for 2-4 hours.

9. A honing stone with ordered abrasive grain arrangement prepared by the manufacturing method according to any one of claims 1-8.

Citation Information

Patent Citations

  • Honing abrasive belt

    CN102229097B

  • A method for tungsten plating on diamond surfaces

    CN103388142B

  • Preparation method of mixed ultra-hard honing oil stone

    CN105803248A

  • Diamond grinding tool and preparing method thereof

    CN109352542A

  • Cutting tool and manufacturing method for same

    WO2009125931A2